Pengembangan Model Pembelajaran Digital Intelegent Tutoring System - Muhammad Yusuf; Andi Cici Thania; Maulida Sari Harahap; Marito Ritonga (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
Intelligent Tutoring System (ITS) is a computer application that has Artificial Intelligence. One of the advantages of ITS compared to conventional teaching is because ITS uses a one-to-one approach between ITS and students. Learning in the classroom is not effective when the understanding between students is not the same. ITS can eliminate student boredom because ITS teaching is more individual and focuses directly on the point of the problem. The purpose of this article is to find out how the Intelligent Tutoring System learning model is implemented in schools. The method in this research is a literature study method with qualitative approach by examining the concepts related to the ITS Model. ITS helps students understand a material and can repeat the material repeatedly until he masters the material. This model is academic assistance or tutoring by tutors to students to help smooth the independent learning process of students individually or in groups related to teaching materials. To be able to carry out one-to-one teaching, the ITS model must be able to recognize these students and build a model regarding their level of knowledge, skills and desires. The system must be able to provide individual instructions or teaching materials to student